Household debt and social interactions - Dimitris Georgarakos; Michael Haliassos; Giacomo Pasini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
Debt-induced crises, including the subprime, are usually attributed exclusively to supply-side factors. We examine the role of social influences on debt culture, emanating from perceived average income of peers. Utilizing unique information from a household survey representative of the Dutch population, that circumvents the issue of defining the social circle, we consider collateralized, consumer, and informal loans. We find robust social effects on borrowing, especially among those who consider themselves poorer than their peers; and on indebtedness, suggesting a link to financial distress. We employ a number of approaches to rule out spurious associations and to handle correlated effects.
urn:nbn:de:hebis:30:3-240863
Keywords: G11; E21; 330; Household Finance; Household Debt; Social Interactions; Mortgages; Consumer Credit; Informal Loans; Private Finanzplanung; Private Verschuldung; Soziale Beziehungen; Soziale Gruppe; Niederlande